Arithmetic, geometry, cryptography and coding theory : 15th International Conference Arithmetic, Geometry, Cryptography and Coding Theory, May 18-22, 2015, CIRM, Luminy, France - International Conference "Arithmetic, Geometry, Cryptography and Coding Theory"; Bassa, Alp; Couvreur, Alain; Kohel, David R. (Contemporary mathematics, 2017)
This volume contains the proceedings of the 15th International Conference on Arithmetic, Geometry, Cryptography, and Coding Theory (AGCT), held at the Centre International de Rencontres Mathematiques in Marseille, France, from May 18-22, 2015. Since the first meeting almost 30 years ago, the biennial AGCT meetings have been one of the main events bringing together researchers interested in explicit aspects of arithmetic geometry and applications to coding theory and cryptography. This volume contains original research articles reflecting recent developments in the field.